The struggle of Tengger Tribal youths using higher education to get social and cultural status in society - Lenny Raficha Fatjerin; Tuti Budirahayu (Jurnal Sosiologi Dialektika, 2021)
The enrollment rate for the higher education of the Tengger tribe is low. However, there is a group of Tengger youths who have the determination to achieve a Bachelor’s degree despite the limitations that they encounter. This study aimed to describe the meaning of education among the Tengger tribe and the efforts of the Tengger youths to continue their studies in college. This study was conducted in Ngadiwono Village Pasuruan Regency in the East Java Province and using a qualitative method. The data is analyzed by social and cultural reproduction theory by Pierre Bourdieu. The data was obtained from bachelor students and people from the older community group in order to find out the meaning of education based on their understanding. The data was collected using interviews, observations and documentation methods. The results of this study show that the success of the youths in becoming undergraduates was due to their effort and hard work. They were supported by their families who had a better understanding of the meaning of education. They have a social modal that they got from elementary education. They develop their social capital to get better education and occupations in the future.